Effect of stress on NiO reduction in solid oxide fuel cells: a new application of energy‐resolved neutron imaging. (1st April 2015) - Makowska, Małgorzata G.; Strobl, Markus; Lauridsen, Erik M.; Frandsen, Henrik L.; Tremsin, Anton S.; Kardjilov, Nikolay; Manke, Ingo; Kelleher, Joe F.; Theil Kuhn, Luise
<x xml:space="preserve">Abstract</x> Recently, two new phenomena linking stress field and reduction rates in anode‐supported solid oxide fuel cells (SOFCs) have been demonstrated, so‐called accelerated creep during reduction and reduction rate enhancement and nucleation due to stress (Frandsen et al., 2014). These complex phenomena are difficult to study and it is demonstrated here that energy‐resolved neutron imaging is a feasible technique for combined mechanics–chemical composition studies of SOFC components, including commercially produced ones. Cermet anode supports, which prior to the measurements were reduced under varying conditions such as different temperatures, various times and different values of applied stress, have been measured. Thus, samples with different contents (and gradients) of Ni and NiO phases were investigated. The first Bragg edge transmission neutron measurements applied for the studies of the reduction progress in these samples were performed at two neutron beamline facilities (ISIS in the UK, Helmholtz Zentrum Berlin in Germany). The obtained results demonstrate the possibility to image and distinguish NiO and Ni phases within SOFC anode supports by energy‐resolved neutron imaging and the potential of the neutron imaging method for in situ studies of reduction processes.